Global research status and trends of bronchiectasis in children from 2003 to 2022: A 20-year bibliometric analysis - Gong, Ting; Wang, Xueer; Li, Shuanglian; Zhong, Li; Zhu, Lin; Luo, Tingting; Tian, Daiyin (Frontiers in Pediatrics, 2023)
Background This study aims to analyze the research hotspots, evolution, and developing trends in pediatric bronchiectasis over the past 20 years using bibliometric analysis and visualization tools to identify potential new research directions. Methods Publications related to bronchiectasis in children were retrieved from the Web of Science Core Collection (WoSCC) database from 2003 to 2022. Knowledge maps were performed through VOSviewer1.6.18 and CiteSpace6.1 R2. Results A total of 2,133 publications were searched, while only 1,351 original articles written in English between 2003 and 2022 were incorporated. After removing duplicates, we finally included 1,350 articles published by 6,593 authors from 1,865 institutions in 80 countries/regions in 384 different academic journals with an average citation frequency of 24.91 times. The number of publications shows an extremely obvious binomial growth trend. The majority of publications originated from the United States, Australia, and England. The institutes in Australia, especially Charles Darwin University, published the most articles associated with pediatric bronchiectasis. In addition, Pediatric Pulmonology was the most published journal. In terms of authors, Chang AB was the most productive author, while Gangell CL had the highest average citation frequency. The five keywords that have appeared most frequently during the last two decades were “children,” “cystic fibrosis,” “bronchiectasis,” “ct,” and “pulmonary-function.” According to keyword analysis, early diagnosis and intervention and optimal long-term pediatric-specific management were the most concerned topics for researchers. Conclusion This bibliometric analysis indicates that bronchiectasis in children has drawn increasing attention in the last two decades as its recognition continues to rise, providing scholars in the field with significant information on current topical issues and research frontiers.